Strengthening performance of PALF-epoxy composite plate on reinforced concrete beams - Chin, Siew Choo; Doh, Shu Ing; Jolius, Gimbun; Siregar, J. P.; Foo, S. Tong; Huey, R. Ong (IOP Publishing, 2018)

(untitled)
This paper presents the effective strengthening potential of pineapple leaves fiber (PALF)-epoxy composite plate on reinforced concrete (RC) beam. At first the PALF is treated with alkali (NaOH) and its morphology is observed via scanning electron microscope (SEM).The composite plates made of PALF and epoxy with fiber loading ranging from 0.1 to 0.4 v/v was tested for its flexural behaviour. The composite was then used for external RC beam strengthening. The structural properties of RC beams were evaluated and all the beams were tested under four-point bending. It was found that the flexural strength increased as the fiber volume ratio increases. The maximum flexural strength (301.94 MPa) was obtained at the fiber volume ratio of 40%. The beam strengthened with PALF-epoxy composite plate has a 7% higher beam capacity compared to the control beam. Cracks formed at the edge of the plate of PALF-strengthened beams resulted in diagonal cracking. Result from this work shows that thePALF-epoxy composite plate has the potential to be used as external strengthening material for RC beam.